Orthodontic treatment consideration in thyroid disorders patients: Pertimbangan perawatan ortodonti pada pasien dengan gangguan tiroid - Ita Purnama Alwi; Eddy H. Habar; Nasyrah Hidayati; Andi S. Permatasari; Rifaat Nurrahmah (Makassar Dental Journal PDGI Makassar, 2026)
Thyroid disorders, including hyperthyroidism, hypothyroidism, and autoimmune thyroid disease, have a significant systemic impact on skeletal metabolism, bone remodelling, and periodontal tissue because orthodontic tooth movement depends on the balance of osteoclast and osteoblast activity within the pe-riodontal ligament and alveolar bone. Disorders at the thyroid hormone level can affect the biomechanics of treatment, the rate of tooth movement, ancho-rage control, and risks during treatment. This article discusses how thyroid dysfunction affects orthodontic tooth movement, periodontal tissue response, bone remodelling, and considerations for orthodontic treatment planning. It is concluded that management should be based on the identification of biological mecha-nisms, treatment risks, and essential clinical considerations for orthodontists treating patients with thyroid disorders.